Correction: Shi et al. Dynamic Scenario Simulations of Sustainable Rural and Towns Development in China: The Case of Wujiang District. Sustainability 2023, 15, 8200 - Shi, Qingwei; Li, Zhiguo; Xu, Yu; Yan, Tiecheng; Chen, Mingman (Sustainability, 2023)
In the original publication [...]